O que se diz e o que se faz : os significados do casamento, relacionamentos amorosos e infidelidade para jovens adultos solteiros - Aragão, Rachel Lilienfeld (2015)
The way of thinking of the world and social relationships has changed in the last 60 years. The relativism of values generated an ambiguity that is evidenced in romantic relationships that have also changed and taken multiple configurations, becoming more liquid and fluid. In this context, this work was developed from a systemic perspective with the objective to understand the meanings of marriage, romantic relationships and infidelity among single young adults. This work intersects the horizontal and vertical flows from current and intergerational perspectives in family life cycle. To obtain these results, this paper consisted of qualitative research, developed by semi-structured interviews and genograms with two men and two women, between 25 and 34 years, which represent Generation Y, currently in the university or with a university degree. The results indicate that marriage, as well as stable union are seen as a choice not an obligation. Romantic relationships are guided by partnership and equality, governed by the concept of pure relationship that provides mutual satisfaction and the possibility of separation when these conditions are not fulfilled. Infidelity presents itself with traditional meanings and some gender issues emerge, given that the male lightness enables an easy break up, against female insecurity, marked by ambiguity that is observed in different meanings assigned to commitment. When considering the intersection of horizontal and vertical flows, it is evident that these representatives of Generation Y were raised in new families arrangements and their idea of intimate relationships were constructed based on cultural concepts of pure relationships and the beliefs and values that came from their families. This process reveals that the relationships are not as liquid as they should appear and not that pure as imagined